Bacterias Isolated from Commercial Avian Clinical Cases Inactivated with a Long Acting Electro Oxidized Water (LEOW) - Paez- Esquilinano, David; Casaubon, Marie Therese; Fuentes-Hernández, Victor Octavio (RA Journal of Applied Research, 2022)
In this work isolated bacteria from avian clinical cases, the antibacterial effect of a long acting Electro Oxidized Water (LEOW) (90 days after fabrication), LEOW was diluted with distilled or/and tap hard water and tested against suspensions of bacterial strains isolated from avian clinical cases (E. coli, Candida albicans, Staphylococcus aureus, and Bacillus subtilis) (in agreement with Mexican sanitary regulations). After fifteen minutes contact with LEOW, the bactericidal effect of LEOW was 99.99% effective. It was concluded that the bactericidal effect a Long acting EOW was not affected by different water qualities and pH, therefore a long acting pH 7.0 LEOW should be considered as an emergent option for the control of pathogens present in food production and animal husbandry. When comparing antibacterial properties with phenol it was observed that LEOW was efficient as/or better that phenol.